Adsorption of Diclofenac Sodium and Ibuprofen by Bentonite Polyureaformaldehyde Thermodynamics and Kinetics Study - Abdel Majeed, Basma Abbas; Muhseen, Raheem Jameel; Jassim, Nawras Jameel (Iraqi Journal of Chemical and Petroleum Engineering, 2018)
An increasing number of emerging contaminants have been detected in surface waters, sediment, soil and ground water in different locations in the world, which is a new environmental challenges need an actual concern for international scientific and legislative communities.    The nonprescription and huge used pharmaceuticals ibuprofen and diclofenac sodium will be focused in this study. New adsorbent developed using cheap inorganic clay material (bentonite) and organic polymer polyureaformaldehyde (PUF), the combination of these two materials gave the surface more roughness with wide active site distribution. Batch adsorption experiment performed to each pharmaceutical individually to determine the optimum separation parameters and understanding the adsorption process pathway. Both pharmaceuticals adsorbed on bentonite –PUF adsorbent in short time ranges from 15 min for ibuprofen to 30 min for diclofenac sodium .Thermodynamic analysis indicates the adsorption process is endothermic in nature and fall in the region of physical adsorption for tested pharmaceuticals (ΔH˚=23.33 and 14.69 KJ/Mol for both ibuprofen and diclofenac sodium respectively).Elovichs equation for describing kinetics of adsorption seemed a good fit with adsorption of both pharmaceuticals .The effect of pH had a significant effect for both pharmaceuticals with high removal (99.8% for diclofenac  and 99.2 % for ibuprofen) at acidic pH=2 below Pka value. Isotherm studied at different initial concentration, the results showed that the Dubinin-Radushkevich model suitable for describing ibuprofen adsorption, and Freundlich's isotherm for diclofenac sodium.